Understanding Québec's Strategic Choices in Domestic and Foreign Debt Markets. (January 2016) - Dzigbede, Komla
Abstract : Much of the discussion on Québec's debt has centered on size and sustainability of provincial debt. As yet, there is no systematic study of the province's strategic choices in debt markets, which choices result in the public debt figures that spawn concerns about debt sustainability among policymakers. This essay attempts to fill that research gap by analyzing the mix of factors that motivate Québec's choice of debt habitat in domestic and foreign markets. Using a menu of estimation techniques, the essay finds that while a mix of bond-specific, institutional, and political factors explains whether Québec issues debt in domestic markets or foreign markets, risk factors in foreign markets tend to have a minimal influence on foreign currency habitat choice. Estimations are based on public accounts data (1960–2014) and information on 160 provincial bonds (1990–2014). Results provide an empirical framework for understanding the structure of debt issuance choices and should feed-forward to policy discussions on the character and sustainability of Québec's debt burden.